Control system of permanent magnet generator using compactrio for SHRE turbine - Che Soh, Azimi (2018)
The SHRE Turbine Generator is developed for one of the alternate applications in remote and rural areas in Sarawak. This system fits the purpose of supplying power electricity based on green energy concept. The turbine floats on the river by pontoons, supported with an anchor system to ensure that the system is sustainable. Additionally, it is equipped with 8 flipping set blades with a complete transmission system including a Permanent Magnet Generator (PMG). Due to money constraints, the 8 Servo motor was replaced with the PMG as an actuator for the controller testing not including the system start-up, shutdown, or supervisory control. It is assumed that the required load is always available for control purposes. The 8 PMG array on the pontoon was on 100% efficiency and the integration between 8 set conversion systems (consisting the AC/DC/AC conversion) should be done. Thus, system monitoring, proper enclosures, processor power, required memory and related concerns are not addressed. The SHRE turbine generator is a hybrid system with the combination of Hydrokinetic System, PV Solar System and stand-alone Diesel Generator (SAD) system and excludes a power storage element. PV Solar energy will be energized at the day time, while the diesel generator (SAD) to be triggered at night time as an supporting energy to the Hydrokinetic System especially when river velocity below than 2.0m/s. The Hydrokinetic System is able to meet any requirement load demand without supporting from PV Solar and SAD if the river velocity over then 2.0m/s. This contributions study outline the development of multiple system turbines cascading 8 PMG from a previous project used in detail to prove that the Intelligent Permanent Magnet Generator Network Control (iPMGNC) control system is workable. It starts from an analysis performance based on LabVIEW software simulation, followed by the parameter measurement and integration between local host (computer) and compactRio, and the implementation of the control strategies/ algorithm on the SHRE Turbine system by using the ac motor simulator. All the controller objectives and strategy were highlighted for: automatically rotating for 8 PMG based on region; the robust CompactRio embedded system; and the smart system protection from rotor over speed under abnormal conditions where it is necessary to avoid the PMG damage.